Removing obstacles to the implementation of LCA among SMEs: A collective strategy for exploiting recycled wool. (10th July 2017) - Testa, Francesco; Nucci, Benedetta; Iraldo, Fabio; Appolloni, Andrea; Daddi, Tiberio
Abstract: Although SMEs often have financial restraints that prevent them from adopting proactive environmental strategies, they are increasingly being pressurized to adopt a more sustainable production pattern. We investigated how SMEs can respond to such external pressures, by studying the fashion industry located in an industrial cluster of Prato (Italy). The adoption of a life cycle assessment (LCA) is taken as representative of proactive environmental action, andthis paper describes a scheme developed jointly by companies and the chamber of commerce in order to overcome the barriers usually faced by SMEs. The study thus demonstrates how SMEs can work with their major stakeholders in response to this external pressure. It also shows how the collaboration between actors operating in the same cluster can support the adoption of an LCA. The results contribute to the literature on institutional theory on effective approaches that support environmental practices. Highlights: An Action research approach was applied for exploring LCA adoption among SMEs. A collaborative strategy can be adopted for overcoming SMEs constraints. LCA works also as a marketing tool. SMEs and local stakeholders work together for spreading LCA implementation.